CONCEPT MAPS AS AN EFFECTIVE FORMATIVE ASSESSMENT TOOL IN BIOLOGY AT SECONDARY LEVEL - Choudhary, Farkhunda; Bano, Rukhsana (Journal of Education and Educational Development, 2022)
Concept mapping has been identified as an effective method that promotes critical thinking in students. The study was conducted to investigative the effectiveness of concept maps as formative assessment tool in Biology at secondary level. The main objective of the study was to investigate how effective concept maps are as an effective formative assessment tool in teaching and learning of concepts in Biology at secondary level. To guide the proposed study a null hypothesis was designed with an alternative hypothesis and tested at level of significance0.05. The research design opt to conduct the study was one group pre-test post-test quasi-experimental design. To complete the study seven weeks was utilized. The sample for this study consisted of students (n=46) of a private girl’s school in Karimabad District Hunza. Data for this study was collected by conducting Bioenergetics Diagnostic Test at each interval with and without intervention. The major findings of the study include; concept maps are important for developing clear understanding of concepts in Biology, concept maps refrains rote learning thus promotes critical thinking and reasoning ability and acts as an effective classroom instructional tool along with formative assessment tool. It was concluded that the concepts maps can be used as an effective formative assessment tool in Biology at secondary level.
Keywords: Concept maps, Formative assessment, Science learning